A Conceptual Study on Shukragata Vata (Premature Ejaculation) – A Review - Bhardwaj, Anant; Sharma, Pankaj (International Research Journal of Ayurveda & Yoga, 2025)
Premature ejaculation (PE) is a common male sexual disorder that is frequently overlooked and resulting untreated. PE is defined as ejaculation before the completion of satisfactory sexual activity for both partners. In Ayurveda, various Acharyas (scholars) have contributed their insights and perspectives to understand diseases and their treatment. This clinical condition is described under Shukragatavata in Ayurveda which is a distinct pathological entity characterized by a group of clinical presentations related with ejaculation impairment and seminal abnormalities among which Sheeghram Munchati (PE) is one. The pathology of the same occurs at three levels of spheres – Sukra, Vata, and Manah. As Shukra is the seventh and final Dhatu, as a Saara (Essence) of all Dhatu, formed by a progressive evolutionary metamorphosis. It is responsible for all systemic bodily processes, including metabolic functions, and a portion of it exits the body during sexual acts which promotes Garbhotpadana (Reproduction). Like Shukra Dhatu, Vata is described as the source of life and the supporter of all living processes, ensuring a long and disorder-free life. Vata also restrains and impels all mental activities, and is responsible for the functional state of mind. All Indriyas (including Upastha) are under the control of Manah and Manah itself is under the control of Vata. All these concepts, that is, Shukra, Vata, and Manah attained superior considerations in Ayurvedic classics. Various ways were also described in ancient Indian erotic literature to trigger orgasm in a female partner, as well as the usage of Shukra Stambhaka medications to enhance control over ejaculation. The intention of this article is to provide a description of Shukragata Vata (PE) in ancient Indian erotic literature and Ayurveda.